Overcoming psychological insulin resistance: A practical guide for healthcare professionals. Issue 3 (June 2021) - Snoek, Frank J.; Fisher, Lawrence; Polonsky, William H.; Stuckey, Heather; Hessler, Danielle; Tang, Tricia; Hermanns, Norbert; Mundet, Xavier; Silva, Maria; Sturt, Jackie; Okazaki, Kentaro; Hadjiyianni, Irene; et al.
Highlights: Psychological insulin resistance is common among people with diabetes. Concerns relate to side effects, efficacy, injection fears, and feelings of failure. HCPs play a critical role to help patients start, and persist on, insulin treatment. HCPs should explore and address the patients' concerns early on in treatment. HCPs should engage patients in their treatment decisions and provide support. Abstract: Despite the demonstrated benefits of using insulin, nearly a third of the patients with type 2 diabetes (T2D) are initially reluctant to initiate insulin therapy when it is first recommended by their healthcare provider (HCP). Several studies have documented the reasons for this phenomenon known as psychological insulin resistance (PIR) and also identified actionable strategies for HCPs to assist people with T2D to overcome their PIR. However, most strategies are based on the experiences of HCPs, rather than of patients. Based on findings from a study exploring real-world patient experience around HCP actions for mitigating PIR, we suggest that HCPs use collaborative strategies throughout the course of T2D treatment to 1) explore reasons for PIR, 2) help patients overcome PIR, and 3) follow-up regarding experience with insulin.